Bench-scale studies of a permeable reactive barrier system for radiocesium removal - Cevikbilen, Gokhan; Camtakan, Zeyneb (Copernicus GmbH, 2020)
Permeable reactive barrier (PRB) technology is being introduced as an alternative method for controlling and treating the groundwater, contaminated with heavy metals, chlorinated organics and radionuclides, etc. To regulate the cost of PRB technology to minimum in line with regulatory decontamination requirements for the contaminants, reactive media should be readily available at a low level of moderate cost. The proposed media included Zeolite (Clinoptilolite) and Sepiolite both as natural raw materials. In this work, we propose to investigate an alternative permeable barrier system for controlling and preventing the migration of radio cesium into the groundwater. It is understood that the falling head type vertical permeability tests performed on the reconstituted raw materials in a special odeometer test device under several vertical pressures might be inadequate to model the natural horizontal flow without mechanical assistance through the barrier in the aquifer. The bench- scale PRB demonstration system were also designed to investigate the horizontal 2D flow of groundwater by supplying a constant difference in between total heads of upstream and downstream. The hydraulic conductivity of the saturated media was studied by a flow net analysis. The effect of the simulated continuous release of contaminant solution in the upstream was observed in the soil media not only at the downstream both also in the upstream and PRBs. Remediation process over time can lead to changes in the hydraulic conductivity of a PRB. The bench-scale PRB system will be used to approximate the operating conditions for the information on the transport behavior of the radio cesium andchange in the hydraulic conductivity in PRB system.